2004
DOI: 10.1021/ol049430a
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Heck Reaction with PCP Pincer Palladium(II) Complexes

Abstract: [reaction: see text] The Heck reaction of phenyl halides with styrene using a series of related PCP pincer palladium(II) complexes was studied in order to evaluate the effect of ligand structure and electronics on the catalytic activity and to investigate the nature of the catalyst species. We suggest these pincer complexes are precatalysts for highly active forms of metallic palladium. This conclusion is based on kinetic studies (induction periods, sigmoidal kinetics), Hg drop tests, quantitative poisoning ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
120
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(124 citation statements)
references
References 25 publications
4
120
0
Order By: Relevance
“…[21] Together these studies provide convincing evidence that these SCS palladacycles and other palladacycles are neither the catalytically active species nor a reversibly formed rest state of an active catalyst for Heck catalysis but rather are a precursor of another undefined but quite active catalyst.…”
Section: Introductionmentioning
confidence: 86%
“…[21] Together these studies provide convincing evidence that these SCS palladacycles and other palladacycles are neither the catalytically active species nor a reversibly formed rest state of an active catalyst for Heck catalysis but rather are a precursor of another undefined but quite active catalyst.…”
Section: Introductionmentioning
confidence: 86%
“…[59] Similar results were obtained on phosphite PCP pincers at the same time we reported on decomposition in SCS pincers. [41] Again, it was not possible to rule out small amounts of catalysis by intact metalligand complexes in that work, although it was clear that the vast majority of catalysis was promoted by Pd(0) species (nanoparticles, it was suggested). In contrast, by immobilizing SCS and PCP pincer complexes onto insoluble porous silica supports and soluble poly(norbornenes), it was possible to conclusively show for the first time that there was effectively no catalysis by intact pincer species.…”
Section: Poly(4-vinylpyridine) As a Poisonmentioning
confidence: 93%
“…Thus, in many contributions, authors have identified catalysis by soluble species but could not rule out some catalysis by supported sites. The Hg(0) test is capable of extinguishing catalysis by free Pd(0), [8,[22][23][24]26,40,41] although it is not believed that it can discriminate between heterogeneous, macroscopic palladium particles, soluble palladium nanoparticles, or homeopathic [35,36,42,43] palladium (vide supra). [8] What is needed is a poison that is selective for leached, homogeneous species.…”
Section: Introductionmentioning
confidence: 99%
“…The Heck reaction has been demonstrated to find wide utility in both, total syntheses of natural products in academia and synthesis in pharmaceutical and agrochemical industry [1][2][3][4][5][6][7][8][9][10] . Even though recent developments have considerably increased the activity of Heck catalysts [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] , a typical reaction protocol with aryl bromides as substrates still requires high reaction temperatures (140 °C), catalyst loadings in the range of 1 mol% and reaction times of up to 24 hr. Moreover, modified reaction conditions, including the reaction temperature, catalyst loadings, bases, solvents, and additives, e.g.…”
Section: Introductionmentioning
confidence: 99%